1984
DOI: 10.1126/science.6547247
|View full text |Cite
|
Sign up to set email alerts
|

Allylamine Derivatives: New Class of Synthetic Antifungal Agents Inhibiting Fungal Squalene Epoxidase

Abstract: A new class of synthetic antifungal agents, the allylamines , has been developed by modification of naftifine , a topical antimycotic. SF 86-327, the most effective of these compounds so far, is highly active in vitro against a wide range of fungi and exceeds clinical standards in the oral and topical treatment of guinea pig dermatophytoses. SF 86-327 is a powerful specific inhibitor of fungal squalene epoxidase, a key enzyme in sterol biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
156
0
5

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(167 citation statements)
references
References 12 publications
3
156
0
5
Order By: Relevance
“…A similar effect has been described in Acerpseudoplatanus tissue culture cells treated with the sterol biosynthesis inhibitor compactin (Ryder & Goad, 1980). The residual biosynthesis in C. albicans was most probably due to methylation of sterol originating from precursors distal to squalene epoxidase, the primary point of inhibition by the allylamines (Ryder, 1984;Petranyi et al, 1984). This is supported by the earlier finding that ergosterol precursors disappear from C. albicans cells treated with a growth-inhibiting concentration of naftifine.…”
Section: Allylamines and Sterol C-24 Methylation I601supporting
confidence: 77%
“…A similar effect has been described in Acerpseudoplatanus tissue culture cells treated with the sterol biosynthesis inhibitor compactin (Ryder & Goad, 1980). The residual biosynthesis in C. albicans was most probably due to methylation of sterol originating from precursors distal to squalene epoxidase, the primary point of inhibition by the allylamines (Ryder, 1984;Petranyi et al, 1984). This is supported by the earlier finding that ergosterol precursors disappear from C. albicans cells treated with a growth-inhibiting concentration of naftifine.…”
Section: Allylamines and Sterol C-24 Methylation I601supporting
confidence: 77%
“…Migration was likely to be only partially disrupted in these 'lipid-deficient' embryos because we were unable to further reduce the function of these enzymes without interfering with the many diverse developmental processes and basic cellular functions that require the products of Hmgcrb and Fntb activities. Interestingly, we also found that the inhibition of Protein geranylgeranyltransferase 1b (Pggt1b) and Squalene epoxidase (Sqle) activities (Petranyi et al, 1984;Vasudevan et al, 1999) partially blocked FBMN migration (see Fig. S2 in the supplementary material), suggesting that both geranylgeranyl protein modification and cholesterol synthesis are required during this process.…”
Section: Research Articlementioning
confidence: 84%
“…Then it was discovered in fungi as an enzyme taking part in ergosterol synthesis and in plants, where it is a part of phytosterols synthesis pathways (Petranyi et al , 1984 ;Godio et al , 2007 ;Rasbery et al , 2007 ;Uchida et al , 2007 ;He et al , 2008;Han et al , 2010 ). SE was also identifi ed in some bacteria which produce pentacyclic triterpens instead of sterols, so-called hopanoids synthesized from squalene by squalene-hopene cyclase (SHC) (EC 5.4.99.17) (Nakano et al, 2003;Pearson et al , 2003 ;Volkman , 2003 ;Nakano et al , 2007 ).…”
Section: Introduction: Squalene Monooxygenasementioning
confidence: 99%